Tahlîlu al-Taqâbul 'an al-Fi'li fî al-Lughah al-'Arabiyah wa al-Injalîziyyah - Bariyah, Khoirul (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2020)
This study covers 3 main problems, namely (1) the definition of verbs in Arabic and English (2) what are the similarities and differences between them (3) how to predict problems regarding verbs in Arabic. This study uses a qualitative study of literature. All data in this study were generated through the documentation method and to analyze the data researcher using a descriptive approach by comparing verbs in Arabic and English. And the results of this study indicate that verbs in Arabic and English are every word that indicates something that happened at a certain time. But between the two have similarities and differences. The similarities between the two are in the aspects of definition, sign, and division. The differences include division and marks. Verbs in Arabic are divided into 3, while in English are divided into 4. Verbs in Arabic and English also have different characteristics. The prediction of the problem about verbs in Arabic when teaching them to students is that verbs which have differences will be difficult for students to understand, while verbs that have similarities will be easily understood by students.